Neuroprotective effects of kobophenol A against the withdrawal of tropic support, nitrosative stress, and mitochondrial damage in SH-SY5Y neuroblastoma cells - Lee, Sung Ryul; Kwak, Jong Hwan; Kim, Hyoung Ja; Pyo, Suhkneung (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
This study examined the neuroprotective effects of kobophenol A (kob A), oligomeric stillbene, and a resveratrol tetramer. Neuronal death induced by the withdrawal of tropic support was ameliorated by kob A. The protective effect of kob A against nitrosative/oxidative or mitochondrial damages resulted in the inhibition of the ROS, intracellular calcium ion level, and mitochondrial transmembrane potential changes on SH-SY5Y cells. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: NITRIC-OXIDE; INDUCED APOPTOSIS; OLIGOSTILBENES; PARAQUAT